Spatial distribution of effective coverage of child immunisation in Ethiopia - Daniel Gashaneh Belay; Melaku Birhanu Alemu; Samrawit Birhanu Alemu; Aynalem Belay (BMJ Public Health, 2025)
Introduction Child immunisation is a cost-effective strategy to reduce vaccine-preventable diseases. While effective coverage is key to ensuring quality immunisation, little is known about its geographical distribution in Ethiopia. This study aims to assess the spatial distribution of effective coverage of child immunisation and identify areas with low coverage to inform targeted interventions.Methods We used the 2019 Ethiopia Mini Demographic and Health Survey and Ethiopia Service Provision Assessment datasets. After calculating the effective coverage of immunisation, Bayesian model-based geostatistics were employed to assess the spatial distribution of effective immunisation coverage in Ethiopia, using relevant covariates to estimate coverage rates across regions.Results The national effective coverage of immunisation was 34% (95% CI: 31.9% to 36.5%), with significant regional variation. Addis Ababa, western Benishangul-Gumuz, Dire Dawa city administrative, the northern part of South West Ethiopia and the northwest part of Amhara had hotspots for high level of effective coverage of child immunisation. On the other hand, central Amhara, northern Gambela, central Oromia, Sidama, northern Southern Nations, Nationalities and Peoples regions (SNNPR) and Somali had low effective coverage of child immunisation. Travel time to the nearest city (−0.292: 95% CI:−0.533 to −0.052) was found to be negative predictor of spatial distribution.Conclusion There were significant geographical variations in the effective coverage of immunisation services in Ethiopia. Travel time to nearest city was a significant predictor of spatial distribution. Policymakers are advised to prioritise underserved areas and improve spatial predictors to have a safe, effective and life-saving vaccination program in Ethiopia.